Assessing diffusion in enzyme loaded sol-gel matrices - Barreira, Gustavo; Ferreira, Ana S. D.; Vidinha, Pedro; Cabral, Joaquim M. S.; Martinho, Jose M. G.; Lima, Joao Carlos; Cabrita, Eurico J.; Barreiros, Susana (Rsc Advances, 2014)
n/a
vidinha, Pedro/H-3426-2013; Lima, Joao Carlos/K-2890-2014; Barreiros, Susana/A-7892-2012; Martinho, Jose/E-1988-2013; Lima, Joao/F-3658-2010; Institute of Chemistry - USP, Dept. of Chemistry/B-8988-2012; Cabrita, Eurico/E-8053-2011; Ferreira, Ana/C-9598-2013 vidinha, Pedro/0000-0002-3907-4969; Barreiros, Susana/0000-0002-7268-5892; Martinho, Jose/0000-0003-1806-1568; Lima, Joao/0000-0003-0528-1967; Cabrita, Eurico/0000-0002-0720-2751; Ferreira, Ana/0000-0001-9381-588X 0